Modelling and integration of multi-parallel organic Rankine Cycles into total site - Chu, Zheng; Zhang, Nan; Smith, Robin (Energy (Oxford), 2022)
Organic Rankine Cycle (ORC) is a promising technology for exploiting the industrial low-grade waste heat. When trying to implement ORCs, proper integration with background waste heat sources is one of the crucial matters that should be considered. Research on ORC integration has been carried out during the last few decades. However, it is observed that the existing methodologies for integrating ORCs into industrial sites are still insufficient. Lots of the research efforts deal with ORC integration problems assuming only one single ORC participates, while the options of applying multi-parallel ORCs are rarely taken into account. Besides, existing research mainly focuses on the direct integration of ORC(s) (i.e. waste heat is transferred directly from heat sources to ORC working fluids), whereas the option of utilizing intermediate heat carriers indirectly is neglected. As such, this study proposes a model-based methodology for the indirect integration of multi-parallel ORCs. The overall model covers both waste heat extraction and ORC power generation. For heat extraction modelling, a modified superstructure based on (Isafiade and Fraser, 2008) [1] is proposed, which simplifies the construction of a heat extraction network (HEN) and reduces computational time. For thermodynamics, the Peng-Robinson Equation of State is adopted. The overall model leads to a mixed-integer nonlinear programming (MINLP) problem and can be solved by a General Algebraic Modelling System, e.g., the GAMS software. Two case studies are performed in this work to validate and illustrate the application of the proposed method, the results of which show that applying multi-parallels ORCs instead of using a single ORC can decrease the overall annualized cost effectively. •A methodology for integrating multi-parallel ORCs with Indirect heat transfer.•An improved superstructure for synthesis the network of ORC integration.•Rigorous thermodynamic correlations for modelling ORC's performances.•A mixed integer non-linear programming optimisation problem.•Case study presented to illustrate the application of the proposed methodology.